2007
DOI: 10.1080/09540120701235669
|View full text |Cite
|
Sign up to set email alerts
|

The effect of homelessness on hospitalisation among patients with HIV/AIDS

Abstract: The purpose of this study was to determine the effect of homelessness on the costs and patterns of hospitalisation in patients with HIV/AIDS. A retrospective longitudinal study design, based on medical records data covering 2,768 person-years of observation between 1997 and 2003 on patients with HIV/AIDS, was employed. A contextual measure of neighbourhood socioeconomic status (SES) was also used to uncover differences among low- and high-SES neighbourhood dwellers. The association of homelessness and neighbou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Similarly, even after adjustment for other factors, Black race/ethnicity has repeatedly been associated with increased hospitalization rates 911,38. It has been hypothesized that patients with lower socioeconomic status have increased hospitalization rates39; in this study patients with public insurance were more likely to be hospitalized than those with private insurance. These sociodemographic differences were observed despite adjusting for CD4 count, the major indicator of HIV-related health status.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, even after adjustment for other factors, Black race/ethnicity has repeatedly been associated with increased hospitalization rates 911,38. It has been hypothesized that patients with lower socioeconomic status have increased hospitalization rates39; in this study patients with public insurance were more likely to be hospitalized than those with private insurance. These sociodemographic differences were observed despite adjusting for CD4 count, the major indicator of HIV-related health status.…”
Section: Discussionmentioning
confidence: 86%
“…30 Delays in seeking treatment may result in more frequent and lengthy hospital admissions. 12, 23, 31 Further, previous studies have clearly demonstrated that unstable housing among IDU is associated with hazardous and unhygienic injecting practices that may also predispose individuals to infection. Unsafe injection practices associated with rushed injections in public places include the use of unclean water sources, decreased sanitization of the skin with alcohol prior to injecting, and the preparation of drugs directly in the barrel of the syringe by adding water and “shaking” without cooking or filtering.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic marginalization, in the form of unmet subsistence needs, may drive the acute care usage seen in these subpopulations. 13,14 Food insecurity, the limited availability of nutritionally adequate or safe food, or the inability to procure food in socially acceptable ways, 15 is an important form of socioeconomic marginalization. In the general population, food insecurity has been associated with many adverse health impacts, including poor nutritional status, [16][17][18][19][20][21] depression, [22][23][24][25][26] suicidal ideation, 26 obesity, 27 and increased cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%